FDI entry mode choice and ownership structure in Turkish market: A firm-level analysis - Burçak Polat (Cogent Economics & Finance, 2017)
The choice of a foreign firm's entry mode into a host country is a strategic decision which impacts its future survival and success in other countries. By employing multinomial logit regression, this study aims to investigate the impact of the firm's level of financial data on the entry mode decisions of investors and their ownership structure in Turkey from 2005 to 2012. The empirical findings have revealed that larger firms with high rate of profitability ratios are more likely to choose the full-ownership mode over others. On the other hand, a higher rate of return on equity increases the probability of investors choosing the shared-ownership mode.
Keywords: C25; F21; F23; F24; F29; 330; multinational corporations; entry mode; mergers and acquisitions; foreign direct investment; joint venture companies